Pengaruh Waktu Pelaksanaan Kerja Dan Fasilitas Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Federal International Finance Rantauprapat - Raja Saul Marto Hendry (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study entitled The effect of work execution time and work facilities on employee performance at PT. Federal International Finance RantauprapatLabuhanbatu.This research is a survey research with quantitative approach.The sample was 27 employees.The data collection techniques used were questionnaires, Likert measurement scale and documentation.With data processing techniques validity test, reliability test, correlation, multiple linear regression analysis, and the coefficient of determination by using SPSS 23.0 for windows.Based on the T test for work execution time can be concluded that for thitung of 3.088 while T table 1.703 (t count greater than ttable)which means that the time of work significantly affect the performance of employees and based on the F test for work facilities thitung of 2.338 while T table 1.703 (t count greater than ttable)which means that work facilities have a significant effect on employee performance. Based on the test results F(simultaneous) variable execution time of work and work facilities simultaneously have a significant effect on employee performance, it can be seen from the F count = 8.571 and F Table = 3.40 in this case F count is greater than F table and significant value is 0.002 smaller than the value of alpha 0.05. Based on the value of Adjusted R square of 0.368 or 36.8% shows that simultaneously the time of work and work facilities contributed to the performance of employees by 36.8%, while the remaining 63.2% % explained by other variables that are not proposed in this study.